Motherhood and job: A literature review - Corrêa Oliveira, Silvana (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
The study aimed to review the literature in order to investigate the relationship between motherhood and work. Studies published between 2002 and 2009 were reviewed, and 34 articles were found. Their results were classified into two categories: 1) The impact of motherhood at work, and 2) The impact of work at motherhood. The results revealed several factors involved on this relationship, associated with both characteristics of work/organization and characteristics of personal and social context of the mother, such as type of work, quality of work environment, children age, and family rearrangements, among others. The joint analysis of articles pointed to the possibility of reconciling motherhood and work, especially when family, social, organizational, and political favorable contexts are present.